The Financing Management Paradigm in Developing the Quality of Islamic Educational Institutions - Khomsah, Laili Ila; Yusuf, Moh (International Tatho Academics, 2025)
The problem of education financing is a crucial problem that is not least experienced by Islamic Education Institutions in Indonesia. Madrasah Aliyah Negeri Insan Cendekia Pekalongan City is one example of an Islamic Education Institution which in financing madrasah through the management system is said to be advanced. The purpose of this qualitative study is to describe the financing management paradigm in the quality of education in the institution. The study data were obtained through observation, structured interviews and documentation. After the data were collected, they were analyzed using the stages of reduction, presentation and verification. This study shows that the financing management paradigm in the quality of education at the State Aliyah Madrasah (MAN) Insan Cendekia Pekalongan City includes several aspects, including the preparation of the madrasah revenue and expenditure budget plan through meetings and deliberations with the principles of togetherness and democracy. Then, direct financing is issued by the madrasah to support the implementation of education. Direct costs in madrasah are used to fulfil madrasah routine expenses and non-routine madrasah expenses. Furthermore, the evaluation of financing is done through supervision and inspection. This study confirms that it is also important for the financing management paradigm of faith-based educational institutions to be holistic and measurable.